1999
DOI: 10.1159/000051452
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Diamino-Pyridine Derivative Prevents Excessive Leukocyte Infiltration in Aggravation of Acute Necrotizing Pancreatitis

Abstract: Leukocyte infiltration in the pancreas is involved in the aggravation of acute pancreatitis from edematous phase into necrotic change, and mild disease into severe disease; however, the mechanism responsible for leukocyte accumulation is not fully understood. This study was designed to clarify the mechanism underlying leukocyte accumulation into the pancreas and to elucidate the therapeutic efficacy of a novel diamino-pyridine derivative, IS-741 on leukocyte-endothelial cell interaction using rat necrotizing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…We and others have previously demonstrated the importance of MAC-1 and ICAM-1 for the progression of acute pancreatitis [33][34][35]. In a murine model of acute necrotizing pancreatitis, Yamauchi et al [36] demonstrated a 500% increase of MAC-1 expression on circulating leukocytes in acute pancreatitis. Interruption of neutrophil adherence by using ICAM-1-deficient animals [34] or antibodies against ICAM-1 [33,35,37] in different models of acute pancreatitis has demonstrated that adhesion of leukocytes to endothelium is of essential importance for the evolution of severe acute pancreatitis.…”
Section: Discussionmentioning
confidence: 74%
“…We and others have previously demonstrated the importance of MAC-1 and ICAM-1 for the progression of acute pancreatitis [33][34][35]. In a murine model of acute necrotizing pancreatitis, Yamauchi et al [36] demonstrated a 500% increase of MAC-1 expression on circulating leukocytes in acute pancreatitis. Interruption of neutrophil adherence by using ICAM-1-deficient animals [34] or antibodies against ICAM-1 [33,35,37] in different models of acute pancreatitis has demonstrated that adhesion of leukocytes to endothelium is of essential importance for the evolution of severe acute pancreatitis.…”
Section: Discussionmentioning
confidence: 74%
“…In both these models, the neutrophil infiltration into the inflamed tissues was significantly reduced by the administration of IS-741. It has also been reported that this new agent decreased the number of adherent leukocytes along pancreatic collecting venules, as well as reducing the expression of Mac-1 (CD11b/CD18) on circulating neutrophils, in an acute pancreatitis model, 15 and it also decreased the number of neutrophils and Mac-1-positive cells accumulated in the injured lung. 17 Based on these results, it appears that the leukocyte accumulation during the early phase of pancreatitis and lung injury may be mediated by leukocyte-endothelial cell interactions via the leukocyte integrin Mac-1, and that this new anti-inflammatory agent attenuated the leukocyteendothelial interactions as a consequence of its inhibitory effect on Mac-1 expression in the inflamed lesions.…”
Section: Discussionmentioning
confidence: 74%
“…[15][16][17][18] However, there are only few reports about the efficacy of leukocyte-endothelial interaction inhibitors against intestinal inflammation. 19 In the present study, we investigated the effects of oral IS-741 on rat experimental ileitis.…”
mentioning
confidence: 99%
“…Through the interaction of adhesion molecules on the surface of neutrophils via vascular endothelium, many more cytokine, chemokine, and free oxygen radicals release (20,21). The deterioration of the microcirculation results as increased permeability of the endothelial layer of the arterioles and venules, leading to extravasation of plasma and erythrocytes presented as edema and microhemorrhagia (19).…”
Section: Hançerli Et Al Efficacy Of Tocilizumab In Pancreatitis Modelmentioning
confidence: 99%